Kemampuan Menulis Karangan Eksposisi Menggunakan Media Gambar Fotografi Siswa Kelas X MIA 2 SMAN 3 Sungai Penuh - Maiza, Suci; Septia, Emil (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2024)
Writing skill is one of the critical linguistic aspects to be developed in language skills. One alternative to attract students' attention and motivation in the learning process is photographic image media. This research objective was to describe the writing skill of an expository essay using photographic image media in class X MIA 2 at SMAN 3 Sungai Penuh. The expository essay included structural aspects, content aspects, and linguistic aspects. The research design was quantitative research with a descriptive method. The research population consisted of 172 students of class X MIA at SMAN 3 Sungai Penuh, with a sample of 36 people. The research instruments were performance tests, observations, field notes, observation guidelines, and assessment sheets. The data collection technique in this research was giving an exposition essay writing test and documentation. The research indicated that the use of photographic image media could help students of class X MIA 2 at SMAN 3 Sungai Penuh in writing expository essays. It could be seen in the results of the exposition writing test of students who obtained a mean score of 81.25 with a percentage of 75% in the capable category.